Notes from the Underground - Editors, The (Pomegranate, 1999)
It is with great pleasure that we welcome back Jenny Blain and Robert Wallis, whose work first appeared in our Fall 98 issue. In this instance, they are the co-authors of an article on the fascinating subject of seidhrwork and gender. Thoseof us who are (still!) running into people who believe that only women can be Witches will be interested in the parallels between this all-too-common misunderstanding and the challenges faced by Heathen men who engaged in the oracular practice of seidhr.